Drammatica della voce. Voice drama - Desideri, Fabrizio (Aisthesis, 2024)
The aim is to show that the “dramatic” character of the voice is not merely about its expressive quality but is intrinsic to its very nature. The voice is “dramatic” because it inherently takes the form of action: it manifests an action. As an expression of an original “theatrum,” the voice is inherently plural, containing “multitudes” (to quote Bob Dylan). On this basis, we will analyze the tension-filled autonomy of the voice with respect to language, and of the vox with respect to the verbum (as per Augustine). Finally, by discussing Derrida, we will address the crucial issue of the relationship between “voice” and “consciousness.”